The Range of Intertextual Resonances - Fagyal, József Szabolcs (Hungarian Journal of English and American Studies, 2021)
Book review: Glazzard, Andrew. Conrad’s Popular Fictions: Secret Histories and Sensational Novels. Hampshire: Palgrave, 2016. 234 pages. ISBN 978-1-137-55916-6. Hb. 95.00.